2018
DOI: 10.1002/jbmr.3537
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived TGF-β Induces Tissue Factor Expression via the Smad3 Pathway in Osteosarcoma Cells

Abstract: Over the last three decades, the prognosis of osteosarcoma has remained unchanged; the prognosis for patients with lung metastasis is still poor, and the development of new treatments is urgently required. We previously showed that aggressive osteosarcoma cells express more tissue factor (TF) and demonstrate enhanced extrinsic pathway capacity. Furthermore, tumor growth can be suppressed with the anticoagulant low molecular weight heparin. However, the molecular mechanisms underlying TF regulation are still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…For example, hepatocyte growth factor (HGF) upregulates TF by activating Met in a Src kinasedependent manner [82]. Other growth factors, including basic fibroblast growth factor (bFGF), platelet-derived growth factor (PDGF)-BB, PDGF-CC, PDGF-AA, bone morphogenetic protein-7 (BMP-7), transforming growth factor-β (TGF-β), and vascular endothelial growth factor (VEGF) can also increase TF [83][84][85][86][87][88][89][90]. During inflammation, TF can be upregulated by a variety of cytokines and signaling molecules, including interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), IL-6, IL-1β, IL-33, and histamine [91][92][93][94][95][96][97][98][99].…”
Section: Regulation Of Tissue Factor Expressionmentioning
confidence: 99%
“…For example, hepatocyte growth factor (HGF) upregulates TF by activating Met in a Src kinasedependent manner [82]. Other growth factors, including basic fibroblast growth factor (bFGF), platelet-derived growth factor (PDGF)-BB, PDGF-CC, PDGF-AA, bone morphogenetic protein-7 (BMP-7), transforming growth factor-β (TGF-β), and vascular endothelial growth factor (VEGF) can also increase TF [83][84][85][86][87][88][89][90]. During inflammation, TF can be upregulated by a variety of cytokines and signaling molecules, including interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), IL-6, IL-1β, IL-33, and histamine [91][92][93][94][95][96][97][98][99].…”
Section: Regulation Of Tissue Factor Expressionmentioning
confidence: 99%
“…Moreover, significant expressions of CD42b, TF, TGF-b, Smad2/3, and p-Smad2/3 were also detected in a biopsy sample from an osteosarcoma patient compared with control. Collectively, these finding suggested that the interaction between osteosarcoma cells and platelets, via thrombin and TGF-b, results in a continuous cycle, and that anti-TGF-b or anti-Smad3 therapy could be a promising tool for disease treatment (Saito et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…( 20 ) Subsequently, we found that platelet‐derived TGF‐β1 increased the expression of tissue factor via Smad3. ( 17 ) These findings suggested that the development of platelet‐targeting therapy is a promising avenue for the treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%